Molecular archaeology of Flaviviridae untranslated regions: duplicated RNA structures in the replication enhancer of flaviviruses and pestiviruses emerged via convergent evolution. - Dmitri J Gritsun (Public Library of Science (PLoS), 2014)
RNA secondary structures in the 3'untranslated regions (3'UTR) of the viruses of the family Flaviviridae, previously identified as essential (promoters) or beneficial (enhancers) for replication, have been analysed. Duplicated enhancer elements are revealed as a global feature in the evolution of the 3'UTR of distantly related viruses within the genera Flavivirus and Pestivirus. For the flaviviruses, duplicated structures occur in the 3'UTR of all four distantly related ecological virus subgroups (tick-borne, mosquito-borne, no known vector and insect-specific flaviviruses (ISFV). RNA structural differences distinguish tick-borne flaviviruses with discrete pathogenetic characteristics. For Aedes- and Culex-associated ISFV, secondary RNA structures with different conformations display numerous short ssRNA direct repeats, exposed as loops and bulges. Long quadruplicate regions comprise almost the entire 3'UTR of Culex-associated ISFV. Extended duplicated sequence and associated RNA structures were also discovered in the 3'UTR of pestiviruses. In both the Flavivirus and Pestivirus genera, duplicated RNA structures were localized to the enhancer regions of the 3'UTR suggesting an adaptive role predominantly in wild-type viruses. We propose sequence reiteration might act as a scaffold for dimerization of proteins involved in assembly of viral replicase complexes. Numerous nucleotide repeats exposed as loops/bulges might also interfere with host immune responses acting as a molecular sponge to sequester key host proteins or microRNAs.